A Computational Model to Automate the Design of Reinforced Concrete Tee Beam Girder Bridge Using Python Ecosystem. Issue 1 (March 2021) - Jain, Utkarsh; Sharma, Mahima; Tumrate, Charanjeet Singh
Abstract: The design of tee beams girder bridge members such as deck slab, main girder, and cross girder is automated by using a computation model based on the python ecosystem. The slab, main girder, cross girder section, and reinforcement detailing are generated by using the purposed computational model. The strength and serviceability checks are as per the Indian Road Congress: 112-2011, Code of Practice for Concrete Road Bridges. The model takes the design parameters of dead and live load from Indian Road Congress 5 and 6 as an input and provides structural detailing of elements involved in the tee beam girder bridge system. The validation of the model architect is performed by comparing it with the solved illustration as per the Indian Road Congress norms. The section sizes and the steel requirement is calculated efficiently and with accuracy thus the time required to generate the structural drawings has reduced drastically. Moreover, with help of the purposed model, a more intensive database of tee beam girder bridges including bridge bearings, piers and foundation can be modelled towards the automation of complete reinforced concrete bridge design as per the Indian Road Congress.